Modelling and performance analysis of amorphous silicon solar cell using wide band gap nc‐Si:H window layer - Haris Mehmood; Tauseef Tauqeer (IET Circuits, Devices and Systems)
Poor charge transport mechanism and light‐induced degradation effects are among the key factors leading to the degraded performance of single‐junction amorphous silicon (a‐Si:H) solar cells. Existent photovoltaic configurations, based on amorphous silicon carbide (a‐SiC:H) window layer, have established efficiencies in the range of 7–10%. Limited performance of such devices has been addressed by replacing a‐SiC:H with a wide band gap (∼2 eV) hydrogenated nano‐crystalline silicon (nc‐Si:H) layer that reportedly exhibits crystalline properties at small scale. Here, the proposed solar cell based on p‐nc‐Si:H/i‐a‐Si:H (buffer)/i‐a‐Si:H/n‐a‐Si:H configuration has been simulated with SILVACO TCAD by analysing window and intrinsic absorber layers thickness, as well as doping concentrations. Along with the engineering of p/i interface, in‐depth evaluation of absorber defects parameters has also been undertaken in order to reduce the recombination rate. The simulated results of an optimised single‐junction device demonstrated an open‐circuit voltage (VOC) of 0.865 V, short‐circuit current density (JSC) of 21.7 mA/cm2, Fill factor (FF) of 0.69 and power conversion efficiency of 12.93%, which is promising when compared with the solar cell already reported. The proposed structure will provide the platform for further development of low cost and efficient multijunction thin‐film amorphous solar cell technology.